Implementasi penilaian otentik dalam pembelajaran Al Qur’an Hadits di MTs Salafiyah Bidayatul Hidayah Mojogeneng Jatirejo Mojokerto - Salim Ashar (PROGRESSA: Journal of Islamic Religious Instruction, 2017)
The problems in this research are: How is the description of the application of authentic assessment in learning Al Qur'an Hadits in MTs Salafiyah Bidayatul Hidayah Mojogeneng Jatirejo Mojokerto ?. How Efforts made by the teacher in applying authentic assessment in learning Al Qur'an Hadits MTs Salafiyah Bidayatul Hidayah Mojogeneng Jatirejo Mojokerto ?. What are the factors that support and obstruct efforts to improve the application of authentic assessment in the study of Al Qur'an Hadits MTs Salafiyah Bidayatul Hidayah Mojogeneng Jatirejo Mojokerto ?. This type of research is field research (field research) in the form of descriptive qualitative research. Instrument used in this research is interview. Therefore, the presence of researchers directly as a benchmark for success to understand the cases studied, so that the involvement of researchers directly and actively with informants and / or other data sources here is absolutely necessary. The results of the research indicate that: 1) the application of authentic judgment in learning Al Qur'an Hadith refers to the assessment of attitude competence through observation, self assessment, peer evaluation by learners and journals, knowledge through written test, test, and assignments, skills through performance appraisals, ie assessments that require learners to demonstrate a particular competence using practice tests, projects, and portfolio assessments. 2) Teachers' efforts in applying authentic judgments in Al Qur'an learning Hadith based on field observations indicate that the scoring system used by teachers generally still uses paper and pencil tests of a small percentage of authentic assessments made by teachers in the form of classroom assessments through performance appraisals, portfolios , product, project, written, and self-assessment. 3) Supporting factors to increase the application of authentic assessment in learning Al Qur'an Hadith: (1) competence possessed by teachers, (2) students' readiness, (3) leadership pattern of headmaster, (4) realization of conducive learning environment, 5) the existence of a laboratory of worship, and (6) the existence of extra-curricular activities. And the inhibiting factors: (1) the lack of socialization of the curriculum of 2013, especially among teachers, given the inadequate timeframe, hastened impression of the national policy on curriculum change from KTSP into the curriculum of 2013, (2) an Hadith is only 3 hours during the week, mainly to measure students' competence achievement in the affective domain, (3) the number of students in one class is big enough, and (4) less optimal participation of parents of learners.